Influenza A Virus NS1 Protein Suppresses JNK1-Dependent Autophagosome Formation Mediated by Rab11a Recycling Endosomes - Kuroki, Takahiro; Osari, Suguru; Nagata, Kyosuke; Kawaguchi, Atsushi (Frontiers in Microbiology, 2018)
Autophagy is an essential process for cellular metabolism and homeostasis, but also functions as one of innate immune responses against pathogen infection. However, in contrast to cellular metabolism and homeostasis pathways, less is known about how virus infection leads to autophagosome formation. Here we showed that influenza A virus NS1 protein inhibits the formation of autophagosomes. The autophagosome formation was induced by infection with NS1 mutant virus lacking the dsRNA-binding activity for inhibition of innate immune responses (R38AK41A) or the activation of PI3K-Akt signaling pathway (Y89F). R38AK41A mutant infection induced phosphorylation of JNK1 and up-regulated the expression of autophagy-related genes which are downstream of JNK1 signaling pathway. We also found that the amount of phosphorylated TSC2, which activates mTOR, increased in wild type-infected cells but not in Y89F mutant-infected cells. These findings suggest that NS1 inhibits the autophagosome formation through both the inhibition of JNK1 and the activation of PI3K-Akt-mTOR pathway. Further, viral ribonucleoprotein (vRNP) complexes were selectively sequestered into autophagosomes, and knockdown of Rab11a, which is responsible for the apical transport of vRNP complexes, impaired not only engulfment of vRNP complexes by autophagosomes but also the formation of autophagosomes in R38AK41A mutant-infected cells. This indicates that Rab11a-positive recycling endosomes function as a donor membrane for the phagophore elongation and an autophagic receptor for the selective engulfment of viral RNP complexes. Based on these results, we propose that NS1 inhibits JNK1-mediated autophagy induction and the sequestration of vRNP complexes into autophagosomes.